Insights from molecular dynamics simulations for interaction between cellulose microfibrils and hemicellulose. Issue 27 (24th June 2022) - Kong, Yi; Li, Libo; Fu, Shiyu
Abstract : The interaction between cellulose microfibrils and xylan is crucial for the strength of the secondary cell wall of vascular plants. Abstract : The interaction between cellulose microfibrils and xylan is crucial for the strength of the secondary cell wall of vascular plants. In this paper, molecular dynamics simulations are used to study the adsorption of xylan on both the hydrophilic (110) and hydrophobic (200) planes of cellulose microfibers and the conformational adaptation of xylan on the plane. The simulation results show that the cellulose and xylan chains are more stable in parallel mode in both planes. The xylan orientation prefers to be parallel with the cellulose microfibrils in the presence of water molecules. The adsorption of xylan on the (110) plane of cellulose microfibrils is dominated by electrostatic interactions, while on the (200) plane, it is dominated by dispersion interactions. The adsorption on hydrophilic planes is superior to that on hydrophobic planes. Meanwhile, a novel independent gradient model is applied to the analysis of weak intermolecular interactions. In addition, a few xylans can adopt a two-fold helical conformation on the (200) plane of cellulose microfibrils. The dominant conformation of xylan in other cases remains the three-fold helix. Xylan is more easily converted to the two-fold helical conformation on the (200) plane than on the (110) plane. The addition of water molecules will reduce the stability of the two-fold helical conformation of xylan.